2008
DOI: 10.1002/clc.20117
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced External Counterpulsation in the Treatment of Chronic Refractory Angina: A Long‐term Follow‐up Outcome from the International Enhanced External Counterpulsation Patient Registry

Abstract: BackgroundThe management of patients who suffer from medically refractory angina and are unsuitable for conventional revascularization therapy is often unsatisfactory. Enhanced external counterpulsation (EECP) is a noninvasive treatment that is safe and effective immediately after a course of treatment. However, the duration of benefit is less certain.HypothesisTo evaluate the 3‐year outcome of EECP treatment.MethodsOne thousand four hundred and twenty seven patients from 36 centers registered in the Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 20 publications
5
38
0
3
Order By: Relevance
“…Previous studies showed that improvement in NYHA class has been associated with a favorable prognosis (22,23). It has been shown that EECP treatment improved symptoms and functional capacity in patients with or without systolic HF (19)(20)(21) therapy (25). The results of our study supported previous studies findings because NYHA class was improved as above mentioned studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies showed that improvement in NYHA class has been associated with a favorable prognosis (22,23). It has been shown that EECP treatment improved symptoms and functional capacity in patients with or without systolic HF (19)(20)(21) therapy (25). The results of our study supported previous studies findings because NYHA class was improved as above mentioned studies.…”
Section: Discussionsupporting
confidence: 90%
“…Sequential inflation of the cuffs, at the onset of diastole, produces aortic counterpulsation and an increase in diastolic pressure while rapid deflation of the cuffs, at the onset of systole, decreases systolic pressure in the vascular system (2). Unlike intraaortic balloon counterpulsation, EECP also increases venous return further, enhancing thus cardiac output (20,21). Furthermore, as diastolic inflation pressure is increased, the preload is increased, afterload is decreased, contractility is increased and mechanical efficiency is neutral (17).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated the long-term effects of EECP. Loh et al (Loh et al, 2008) used the International EECP Patient Registry (IEPR-1) that enrolled consecutive patients treated with EECP in more than 100 centers; follow-up duration was 3 years. These investigators found that immediately post-EECP, the proportion of patients with severe angina (CCS III/IV) was reduced from 89% to 25% (p<0.001).…”
Section: Evidencementioning
confidence: 99%
“…Results from the IEPR and the EECP Clinical Consortium have demonstrated that the symptomatic benefit observed in controlled studies translates to the heterogeneous patient population seen in clinical practice. Moreover, follow-up data indicate that the clinical benefit may be maintained for up to 5 years in patients with a favorable initial clinical response (Lawson et al 2000;Loh et al 2008) Soran et al, compared the efficacy, repeat EECP and 6-months major adverse cardiovascular events (MACE: Death/CABG/PCI/MI) free survival rates for patients treated with EECP for angina management in Europe (EU) with the United States (US); 4658 were treated and followed in the US and 262 in EU. EU were younger (p<0.001) with a higher proportion of men.…”
Section: Eecp Therapy In Cad Managementmentioning
confidence: 99%